Development of flight and foraging behaviour in a juvenile seabird with extreme soaring capacities. Issue 1 (8th November 2019) - Corbeau, Alexandre; Prudor, Aurélien; Kato, Akiko; Weimerskirch, Henri
Abstract: The early life of animals is a period of high mortality, when foraging capacities are assumed to be improved progressively. In birds, this critical period involves the improvement of the flight. How do young birds gain these capacities has rarely been studied in natural conditions especially in seabirds that spend most of their life at sea. We used detailed GPS and body acceleration data on 37 great frigatebirds ( Fregata minor ), to test the hypothesis that juveniles starting their first flights have lower flying capacities than adults, but that these capacities will improve during a long learning period, before independence from parents, specific to this seabird that can spend months on the wing at sea. We found that most flight components improved over time to tend towards those of adults, especially the travel speed, range, duration and maximum altitude of trips. However, unexpectedly, juveniles had higher ascent rates, soaring and gliding capacities above the sea than adults. Moreover, energy expenditure of juveniles was similar to adults during low cost travelling movements and during active foraging, but juveniles spent more time foraging actively than adults. Our results suggest that flight tactics based on long‐distance effortless movements specific to this family are acquired during a long period, but soaring and gliding capacities are already inherited by juveniles and possibly favoured by morphological adaptations specific to juveniles. These adaptations might explain the extreme dispersive capacities of juveniles. Abstract : By combining GPS location, altitude and high frequency accelerometer data the study reports for the first time the development of flight and foraging behaviours of a seabird specialised on soaring flight over the ocean.